2020
DOI: 10.3389/fphys.2020.595086
|View full text |Cite
|
Sign up to set email alerts
|

Expression Regulation and Physiological Role of Transcription Factor FOXO3a During Ovarian Follicular Development

Abstract: In mammals, developing ovarian follicles transform from primordial follicles to primary follicles, secondary follicles, and mature follicles, accompanied by changes in follicular secretory functions. FoxO3a is a member of the forkhead transcription factor family (FoxO), which plays an important role in the cell cycle, DNA damage repair, apoptosis, oxidative stress, and energy metabolism. Recent studies have shown that FOXO3a is involved in the physiological regulation of follicular development and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…It is currently established that Foxo3a can enhance transcriptional regulation of its target genes, thereby inducing oocyte apoptosis, and inhibiting the activation of primordial follicles. Namely, Wnt signaling reduces the number of primordial follicles transformed into mature follicles, thus preserving the follicular reserves ( 52 ). In terms of individual genes, we found that several piRNAs tend to be negatively correlated with genes regulating granulosa cell proliferation and follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently established that Foxo3a can enhance transcriptional regulation of its target genes, thereby inducing oocyte apoptosis, and inhibiting the activation of primordial follicles. Namely, Wnt signaling reduces the number of primordial follicles transformed into mature follicles, thus preserving the follicular reserves ( 52 ). In terms of individual genes, we found that several piRNAs tend to be negatively correlated with genes regulating granulosa cell proliferation and follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GRX2 exerts cardioprotective effects by activating the Nrf2 pathway via upregulation of Akt and GSK-3 β phosphorylation to abate cardiomyocyte apoptosis, oxidative stress, and inflammation in H/R injury [ 26 ]. Akt can regulate the activity of FOXO3a, one of the main downstream effectors of Akt [ 27 ]. H 2 S dampens DOX-induced apoptosis and oxidative stress in cardiomyocytes by heightening phosphorylation of Akt and FOXO3a, thereby attenuating cardiotoxic effects [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…FoxO3a plays a role in the regulation of trophoblast development and pregnancy complications, and a decreased expression of FoxO3a was found in the placenta of PE cases and was present in trophoblasts ( Chen et al, 2021 ). Furthermore, FoxO3a posttranslational modifications were increased by accumulated reactive oxygen species (ROS) under oxidative stress ( Zhang H. et al, 2020 ). Therefore, these results could be an indirect result of this cellular stress induced by L-NAME and more easily controlled with anti-free radical agents such as vitamins C and D. Here, our results showed that the FoxO3a protein level was downregulated in trophoblasts under NOS inhibition.…”
Section: Discussionmentioning
confidence: 99%